Efeito de um programa de treinamento resistido na composição corporal, força muscular e parâmetros bioquímicos em crianças pré-púberes com obesidade - Porto, Marcelo (2011)
Introduction: Obesity affects a large part of the world population, with impact also in childhood. Research has shown that resistance training (RT) has significant role in the prevention and treatment of obesity and its consequences on health and quality of life. Objective: To evaluate the effect of a program of resistance training on body composition, muscle strength and biochemical parameters of children with obesity. Methods: seven male children, aged between 9 and 10 years (mean 10.2 ± 0.8 years), classified as stage 1 of the Tanner scale, were submited to a RT program during 10 weeks, relative intensity between 45-65% of one maximum repetition (RM) and three times weekly. Evaluations were made of muscle strength (10 RM), body composition (body fat percentage by skinfold thickness and ultrasonic evaluation), lipid profile [(total cholesterol, triglycerides fraction of low-density cholesterol (LDL) cholesterol and fraction high-density lipoprotein (HDL)], blood glucose and oxidative stress indicators (Malondialdehyde - MDA and total anti-oxidant defense - TEAC) in the pre and post training. Foi employed Student's t test for paired data for the analysis of means and standard deviations and nonparametric statistical analysis using Mann-Whitney test for determining the differences between to mean values before and after training. Admitted to the significance level for p-value ≤ 0.05. Results: We observed an average increase of 40.25% ± 25.87% in muscle strength, the highest increase was in the gastrocnemius muscles 95% (pre = 15.11 ± 1.02 kg, post = 29.28 ± 4, 49kg, P = 0.001), and a smallest increase in the triceps (11%) (pre = 26.42 ± 6.27 kg, post = 29.28 ± 7.32 kg, P = 0.05). The body composition assessed by ultrasound, a significant reduction of 11% in triceps skinfold thickness, and 6.15% (P = 0.003) subscapular. Biochemical parameters a significant reduction of 26.6% in the levels triglycerides (pre = 93.42 ± 41.76, post = 68.57 ± 20.41 mg /dL, p = 0.01), 6 7% (pre = 80.71 ± 4.49, post = 75.28 ± 4.42 mg /dL, p = 0.03) in the blood glucose, significant increase of 10.5% in HDL (pre = 50.42 ± 12.34, post = 55.71 ± 10.01 mg /dL, p = 0, 01) and 1.61% in TEAC (pre = 2.48 ± 0.02, post = 2 , 52 ± 0.03 nM/L, p = 0.01). The analysis of Pearson's correlation coefficient showed a positive correlation (r = 0.91, p = 0.003) between total cholesterol and LDLc, and negative correlation between triglycerides and TEAC (r = -0.84, p = 0.01). Conclusions: Were also observed resistance training program is effective in inducing positive changes in body composition, such as reducing fat, increasing muscle strength, positive changes in indicators of glucose and lipid profile and improves the body's protection against radicals free and in prepubertal children with obesity.